Resources for the Religion class (II): stories (Journal of Parents and Teachers, 2014)
One of the essential resources for the Religion class are stories, since we can use those offered by the Bible on myths and legends, as well as chronicles and narratives. The aim is to explain events that are incomprehensible to human beings, to transmit a series of values, to try to make them understand the message of Jesus, etc.One of the main advantages of stories is that they are similar to tales and therefore tend to remain in the memory. The main reason is that we feel mirrored or understood.In the following article we offer four stories, one for each year of Infant Education and the last one for Primary Education.
Keywords: educative resources; religion; stories